Laboratory biosafety measures in receiving, preparation and processing of pathology specimens in suspected and positive coronavirus infection - Sekaran, Anuradha; Yandapally, Niharika R.; Vanere, Veena P. (International Journal of Research in Medical Sciences, 2020)
COVID-19, caused by SARS-CoV-2 virus which is declared as a pandemic by the WHO on March 2020 has made a huge difference in the practice and daily activities of the laboratory services. There are high chances of receiving potentially infectious samples to the laboratory for various tests. Authors propose a few biosafety measures in the preparation and processing of various pathology specimens received to the lab during this pandemic time in correlation with guidelines given by WHO. These safety measures aim at protecting and safe guarding the laboratory staff, trainees, and pathologists by minimizing the exposure to COVID-19.